Economic Potential of Coastal Communities in Regional Development in Timbala Village, West Poleang District, Bombana Regency - Hasriyanti, Hasriyanti; Asriyani, Lili; Putri, Ratri Harianti; Bachtiar, Annursyah (Jurnal Geografika (Geografi Lingkungan Lahan Basah), 2024)
This research aims to examine the economic potential of coastal areas as an effort to develop the region in Timbala Village, West Poleang District, Bombana Regency. This study uses a library research type that relies on various literature as sources of research data. The research results can conclud that Timbala Village has great potential for development because it offers various significant opportunities to improve community welfare. With a wealth of natural resources such as fisheries, tourism, and industry, Timbala Village has a strong foundation for local economic development. In addition, its tourism potential, including beaches, coral reefs, and marine biodiversity, can be a driving force for a sustainable economy. Infrastructure development and community empowerment are the keys to optimizing this potential. Through sustainable environmental conservation efforts and wise use of resources, it is hoped that Timbala Village can achieve a higher level of prosperity for its entire community. The synergy between various parties, including the government, community, and private sector, will be the key to success in developing the coastal potential of Timbala Village.